Good and bad Jobs in Greece during the first years of the crisis - Ιωαννίδης, Αλέξης (The Greek Review of Social Research, 2016)
This article utilizes the Jobs Approach methodology, for the first time in Greek economy, to identify the good and the bad Jobs in Greece. It also estimates changes in employment for each Job during the first years of the economic crisis using micro data from the Eurostat’s Labour Force Survey. Among the findings of the article are signs of Jobs polarization in Greek economy at the beginning of the economic crisis.